Analisis Hukum terhadap Benda Jaminan Fidusia yang Digadaikan oleh Debitur Kepada Pihak Lain - Pasaribu, Enni Martalena; Minin, Darwinsyah; Marlina, Marlina; Ramadhan, M. Citra (Universitas Medan Area, 2019)
The research aims to examine the transfer of ownership rights of an object on the basis of trust provided that the object whose ownership rights are transferred remains in the possession of the owner of the object. While the fiduciary guarantee is a fiduciary guarantee institution that can be used to bind the collateral object in the form of movable and immovable objects, especially buildings that cannot be encumbered by mortgage rights. But sometimes the fiduciary collateral is not always the fiduciary giver (debtor) as is mortgaged. Based on this the authors are interested in conducting more in-depth research about collateral objects that are mortgaged by the debtor to other parties. The approach method used in this research is empirical juridical. The data obtained is guided by the empirical aspects that are used as a tool. The research results obtained that the provisions regarding fiduciary guarantees are regulated in the contractual agreement clause by the finance company (PT. SMS Finance and PT BAF Medan Branch) and if not clearly regulated then the provisions of Law Number 42 of 1999 concerning Fiduciary Guarantees apply.